Peran Kepercayaan Pada Hubungan Antara Media Sosial dan Modal Sosial Dengan Keputusan Pembelian Pada Akomodasi di Nusa Penida - Loanata, Cahyo Purnomo; Utama, I Putu; Hardini, Widi (JURNAL MASTER PARIWISATA; Volume 09, Nomor 01, Juli 2022DO - 10.24843/JUMPA.2022.v09.i01.p03, 2022)
This study was conducted to analyze trust as a social media and social capital provided in influencing purchasing decisions. This study aimed to determine the mediating role of trust in the relationship of social media and social capital to purchasing decisions on accommodation in Nusa Penida. This study will discuss the factors that can influence purchasing decisions on accommodation in Nusa Penida. Data were collected using a questionnaire with accommodation guests in Nusa Penida as respondents and 150 respondents. Hypothesis testing using structural equation model (SEM) analysis with the help of the AMOS application. This study concludes that social media (X1) has no effect on trust (Y1), social capital (X2) has no effect on trust (Y1), trust (Y1) has an effect on purchasing decisions (Y2), trust (Y1) has a role mediation on the relationship of social media (X1) to purchasing decisions (Y2) and trust (Y1) has a mediating role on the relationship of social capital (X2) to purchasing decisions (Y2). Findings, purchasing decisions can increase if social media is getting better and guests have a high sense of trust so that in the end purchasing decisions will also increase if social capital is getting better and guests have a high sense of trust so that in the end purchasing decisions will increase. Keywords: social media, social capital, trust, purchase decision.